P , T -odd effects in YbCu, YbAg, and YbAu - Polet, Johan David (2024)
In this work, the molecular enhancement factors of the P,T-odd interactions involving the electron electric dipole moment (W_d) and the scalar-pseudoscalar nucleon-electron couplings (W_s) are computed for the ground state of the bimetallic molecules YbCu, YbAg and YbAu. These systems offer a promising avenue for creating cold molecules by associating laser-cooled atoms. The relativistic coupled-cluster approach is used in the calculations and a thorough uncertainty analysis is performed to give accurate and reliable uncertainties to the obtained values. Furthermore, an in-depth investigation of the different electronic structure effects that determine the magnitude of the calculated enhancement factors is carried out, and two different schemes for computing W_d are compared. The final values for the enhancement factors are (13.32 +/- 0.13) x 10^24 (h Hz)/e cm), (12.19 +/- 0.12) x 10^24 (h Hz)/e cm) and (2.36 +/- 0.48) x 10^24 (h Hz)/e cm) for W_d, and (-48.63 +/- 0.53) h kHz, (-45.68 +/- 0.60) h kHz and (3.81 +/- 2.58) h kHz for W_s, for YbCu, YbAg and YbAu, respectively.